Combined Bulk and Surface Passivation in Dimensionally Engineered 2D‐3D Perovskite Films via Chlorine Diffusion. (11th August 2021) - Mahmud, Md Arafat; Pham, Huyen T.; Duong, The; Yin, Yanting; Peng, Jun; Wu, Yiliang; Liang, Wensheng; Li, Li; Kumar, Anand; Shen, Heping; Walter, Daniel; Nguyen, Hieu T.; et al.
Abstract: Dimensional engineering of perovskite films is a promising pathway to improve the efficiency and stability of perovskite solar cells (PSCs). In this context, surface or bulk passivation of defects in 3D perovskite film by careful introduction of 2D perovskite plays a key role. Here the authors demonstrate a 2D perovskite passivation scheme based on octylammonium chloride, and show that it provides both bulk and surface passivation of 1.6 eV bandgap 3D perovskite film for highly efficient (≈23.62%) PSCs with open‐circuit voltages up to 1.24 V. Surface and depth‐resolved microscopy and spectroscopy analysis reveal that the Cl − anion diffuses into the perovskite bulk, passivating defects, while the octylammonium ligands provide effective, localized surface passivation. The authors find that the Cl − diffusion into the perovskite lattice is independent of the 2D perovskite crystallization process and occurs rapidly during deposition of the 2D precursor solution. The annealing‐induced evaporation of Cl from bulk perovskite is also inhibited in 2D–3D perovskite film as compared to pristine 3D perovskite, ensuring effective bulk passivation in the relevant film. Abstract : A 2D perovskite passivation scheme based on octylammonium chloride provides combined bulk and surface passivation of 3D perovskite film through Cl − diffusion into the 3D perovskite bulk.